Industry 4.0 readiness: a comparative study of Singapore and Indonesia - Kwa, Benjamin Boon Keong (Nanyang Technological University, 2022)
Industry 4.0, otherwise known as the fourth industrial revolution, involves the widespread adoption of emerging technologies in the production space. Examples would include additive manufacturing and the Internet of Things (IoT). Countries worldwide are positioned differently, and also react in a variety of ways when endorsing such rapid changes. Using a case study of two of Southeast Asia’s largest economies, I argue that Singapore is in a stronger position compared to Indonesia with regards to realizing and profiting from this transition. Singapore’s future-oriented government and initiatives, substantial emphasis on education and training, strong foundation in technology and innovation, and open trade policies enable it to be at the forefront in terms of level of readiness. Conversely, Indonesia has room for improvement and risks falling further behind its regional counterpart if it does not adapt its approach to Industry 4.0.